ANALISIS KESULITAN BELAJAR BERDASARKAN GAYA BELAJAR SISWA KELAS X IPA PADA MATA PELAJARAN KIMIA DI MAS AL-MUSTAQIM ARANG LIMBUNG - Ningsih Fatmawati; Rizmahardian Ashari Kurniawan; Tuti Kurniati (Universitas Muhammadiyah Pontianak, 2019)
Learning difficulty is a condition where the students are not able to compherend what they learn so it causes the low exhaustiviness of students learning outcomes. This is caused by various factors, one of them is internal factor, namely learning style which has not been noticed by teacher, because it can help the learning process become faster and easier. This researcher was descriptive research which generally aimed to: (1) determine students learning style based on VARK learning styles, (2) find out students learning difficulty in chemistry subject, and (3) find out students learning difficulty in each type of learning style. The instruments of this research were questionnaire, observation, interview, and documentation. Based on the data analysis, the researcher got the information that the tendency of students learning style were dominated by V-A-R-K learning style (42,87%). There were 75% of students who experienced learning difficulty on the material of chemical calculation (stoichiometry) especially for the indicators in determining calculation based on the basic of chemical laws and morality based on the mole concept. It was due to the teacher tended to use lecture method. Morever, learning difficulty was also because the students have not known learning style they have, so that the students could not focus on learning style but they were more focused on finishing calculation tasks.